Preparation And Characterization Of Silicone Rubber Composites Filled Waste Mineral Fillers For High Voltage Insulation Application - Kamarudin, Najwa (2019)
Silicone rubber (SiR) based composites has increased demand in high voltage (HV) insulator application, due to their exceptional advantages over the existing conventional ceramic based insulator. SiR based insulator has compromised light-weight, superb breakage resistance, improved seismic performance and more flexible and manufacturable, than ceramic insulator. Hence, this research was conducted to prepare and characterize the performance of SiR based composites filled with mineral fillers, that derived from waste resources of silica (SiO2) from waste glass, calcium carbonate (CaCO3) from waste cockle shell and wollastonite (CaSiO3) from combination of both. Simplified calcination heat treatment between SiO2 and CaCO3 (at percentage ratio of 51.70% : 48.30%), has successfully derived synthetic mineral CaSiO3, as confirmed by x-ray diffraction at 37.5°of 2Ɵ peak. Later, SiR filled mineral filler was compounded by internal mixer with addition of dicumyl peroxide (DCP) as vulcanization agent, aux-heat stabilizer as colorant and mineral filler. Vulcanization via hot compression molding was performed before continuing into prolonged post-cured for complete conditioning. Two main independent variables has been tested in this research, which are the effects of mineral filler types and the effects of mineral filler loadings (at 5.00, 10.00, 20.00, 30.00 and 40.00wt.%), towards the resulted electrical, physical, mechanical and morphological performances of SiR filled composites. For electrical testing, an inclined plane test (IPT), surface resistivity and relative permittivity tests were conducted. Fracture surface observation via scanning electron microscope (SEM) was performed to relate the behavior of resulted mechanical strength of produced SiR based composites.It was interestingly found that, addition of mineral fillers caused an improvement in tensile strength about 70%, which exhibited by SiR/CaSiO3 at 5.00wt.% filler added. In terms of IPT test, SiR/CaSiO3 had maximally passed the tracking failure limit (4 out of 5 samples < 2.50cm) as compared than the other SiR composites. In addition, SiR/CaSiO3 at 40wt.% exhibits highest value of surface resistivity and relative permittivity. Not only that, it also possessed maximal hardness value which indicating complete peroxide curing, at before and after HV exposure. While stable water absorption was also obtained by SiR/CaSiO3 sample. In overall, SiR based composites provide absolute significant improvement as compared than unfilled especially for SiR/CaSiO3 composites, which has dominated the best properties almost for entire performed tests. These findings, was underlined the potential of CaSiO3 over the other mineral fillers, to established improved filler-matrix interaction, due to their needle-like structure and protrusion condition and its extraordinary insulation effects, which benefited for electrical insulation and strength performances of SiR based composites for outstanding and reliable HV application.